Responsabilidad penal de los notarios en la celebración de escrituras por partición extrajudicial - Almachi Herrera, Edwin Vinicio (2026)
This research aims to develop a critical legal analysis of the criminal liability of notaries in the execution of deeds involving older adults. This research aims to ensure that notaries protect their rights and not to seek to benefit a third party in the execution of deeds or contracts. The methodology applied was primarily and qualitative, through the analysis of doctrinal and jurisprudential documents. and within legal research, it is dogmatic and legal, examining laws, resolutions, and comparative law. It is oriented toward the study of doctrine as a focus for a basic legal analysis that incorporates into notarial law the power to execute deeds by extrajudicial partition before a notary public involving older adults in vulnerable conditions. Finally, based on the information obtained, it is concluded that in Ecuador, liability in notary offices rests solely with the owner, not with public officials who work there. Therefore, notaries, as representatives of the state, are called upon to provide quality service to users, offering guarantees of truthfulness and reliability.